Presentation of Bilateral Facial Paralysis in Melkersson–Rosenthal Syndrome - Gustavo Gaitan-Quintero; Loida Camargo-Camargo; Norman López-Velásquez; Miguel González (Case Reports in Neurological Medicine)
Introduction. Melkersson–Rosenthal syndrome (MRS) is a neuromucocutaneous disorder characterized by the following classic symptom triad: peripheral facial paralysis, orofacial edema, and scrotal or fissured tongue. It is rare, and since most of the patients are oligo- or monosymptomatic, it makes it difficult to diagnose. Clinical Case. We present a 26-year-old male patient with a history of sickle cell trait, untreated snoring, and left peripheral facial paralysis when he was 11 years old. This was an overall 20-day clinical profile that started with left peripheral facial paralysis, which was accompanied by moderate-intensity occipital pulsatile headaches. Additionally, the patient experienced paresthesias in the tongue and feelings of labial edema. After one week, he manifested peripheral facial paralysis on the right side. Physical examination revealed bilateral peripheral facial paralysis, mild labial edema, and a scrotal or fissured tongue. The patient received corticosteroids, which resulted in improvement of the edema and facial paralysis. Discussion. MRS is a rare disorder that predominantly affects women, typically starting in their 20s or 30s. The etiology is unknown. However, a multifactorial origin that involves environmental factors and a genetic predisposition has been proposed, which causes a dysfunction of the local immune system and autonomic nervous system (ANS) and an appearance of granulomatous inflammation in the lips and tongue. Facial paralysis usually appears later on; however, it can occur from its clinical debut. There are no curative treatments. Therapy is focused on modulating the patient's immune response, and relapses are frequent.